Immune reactivity to neurofilament proteins in the clinical staging of amyotrophic lateral sclerosis. Issue 3 (27th September 2013) - Puentes, Fabiola; Topping, Joanne; Kuhle, Jens; van der Star, Baukje J; Douiri, Abdel; Giovannoni, Gavin; Baker, David; Amor, Sandra; Malaspina, Andrea
Abstract : Background: Neurofilament (NF) proteins detection in biological fluids as a by-product of axonal loss is technically challenging and to date relies mostly on cerebrospinal fluid (CSF) measurements. Plasma antibodies against NF proteins and particularly to their soluble light chain (NF-L) could be a more practical surrogate marker for disease staging in amyotrophic lateral sclerosis (ALS), an invariably fatal and clinically heterogeneous neuromuscular disorder. Methodology: We have used a recombinant neurofilament light chain (NF-L) protein for the ELISA detection of antibodies against NF proteins in plasma samples from a well-characterised cohort of ALS individuals (n:73). The use of an established functional rating scale and of a recently proposed staging of disease progression allowed stratification of the ALS cohort based on disease stage, site of onset, survival and speed of disease progression. Results: Antibody levels to NF proteins in plasma were significantly higher in ALS individuals compared to healthy controls (p<0.001). Higher NF plasma immunoreactivity was seen in advanced ALS cases (stage IVA-B) compared to earlier phases of the disease (p<0.05). There was no difference in anti-NF plasma antibodies between ALS individuals treated with riluzole and untreated patients; although riluzole-treated ALS cases with an earlier age of onset and with a shorter diagnostic delay displayed higher anti-NFL antibody levels compared to untreated ALS patients with similar features. Conclusions: Immunoreactivity to plasma NF-L and homologous NF proteins is informative of the stage of disease progression in ALS. The determination of NF antibody levels in plasma could be added to the growing panel of disease-monitoring biomarkers in ALS targeting cytoskeletal antigens.